2020
DOI: 10.3390/rel11090446
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Generosity: Multi-Level Approaches to Studying the Religiousness of Prosocial Actions

Abstract: This paper provides a meta-analysis of the intersection of (a) religiosity and spirituality with (b) generosity, philanthropy, nonprofits, and prosociality. The study is informed by three informational sources, chronologically: (1) informational interviews with scholars and practitioners based within and studying regions outside of the U.S. and Western Europe; (2) discovery search of purposefully selected extant publications, especially focusing on the last decade of contemporary scholarship; and (3) systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 311 publications
0
9
0
Order By: Relevance
“…Religion and religiosity play a significant role in shaping behaviors, including charitable giving and philanthropy (Dilmaghani, 2018; Herzog et al, 2020; Monsma, 2007). Across various religious traditions, teachings emphasize the importance of compassion, generosity, and helping those in need.…”
Section: Religion As a Social Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Religion and religiosity play a significant role in shaping behaviors, including charitable giving and philanthropy (Dilmaghani, 2018; Herzog et al, 2020; Monsma, 2007). Across various religious traditions, teachings emphasize the importance of compassion, generosity, and helping those in need.…”
Section: Religion As a Social Identitymentioning
confidence: 99%
“…While philanthropy has evolved to encompass a diverse range of motivations and approaches, the enduring legacy of religious traditions continues to inspire acts of generosity and compassion that seek to create a more just and equitable world. Indeed, studies have shown that individuals with religious affiliations and/or higher levels of religiosity exhibit greater propensity for giving, both to religious and secular causes (Herzog et al, 2020; Monsma, 2007). Yet, most DEIJ efforts, like Spanu and Gill's article (Spanu & Gill, 2024) and Duckworth's “wheel of privilege and power” (IRCC, 2022) it is based on, exclude religion and religious minorities from their efforts (Grim & Johnson, 2021; Meitchik, 2023; Razaki et al, 2022); this might be due to the pervasive nature of Christian hegemony and the view of Christianity as the norm.…”
Section: Philanthropies Roots In Religious Traditionmentioning
confidence: 99%
“…However, other researchers limit philanthropy to specific types of actors of activities. Most commonly, philanthropy is restricted to money donations (Harrow, 2010) or donations, bequests and foundations by wealthy people, only (Herzog et al, 2020). Given these various understandings of the scope and content of philanthropy, it can be described as an essentially contested concept (Daly, 2012;Payton & Moody, 2008;Van Til, 1990).…”
Section: Contemporary Philanthropy As Essentially Contested Conceptmentioning
confidence: 99%
“…The first barrier lies in the difficulty in reaching conceptualizations that provide an inclusive understanding of the rich diversity of philanthropic actors and practices around the world and pave the way for future comparative studies. While research on individual philanthropy is skewed toward an understanding of this term as typical of affluent white men (Herzog et al, 2020), research on institutional philanthropy largely concentrates on the undertakings of endowed, grant-making foundations along the US standard (Toepler, 2018). Connected to this, the second barrier relates to the many hurdles involved in collecting and measuring evidence on the economic operations and social performance of philanthropy, as systematic data are scarce except for the US and a few other Western countries (for Europe see Hoolwerf and Schuyt, 2017;Wiepking, 2009); the same geographic locations that, not by chance, dominate the consolidated field of nonprofit studies.…”
Section: Introductionmentioning
confidence: 99%
“…But, in contrast to philanthropy, generosity appears to have a more favorable connotation. In a series of informational interviews with scholars and practitioners from across the world, Herzog et al (2020) conclude that generosity ''is seen to be a softer concept, one that is more concerned with the motivation or values behind the act of giving than with the gift itself.'' (Herzog et al 2020, p. 464).…”
Section: A Future Collaborative Research Agenda: To Come To An Inclusmentioning
confidence: 99%